(untitled) (Revista de Ciências Agroveterinárias, 2018)
The surface distribution of liquid pig manure on the soil aiming crop fertilization is a common activity in pig farms. The objective of this study was to evaluate the soil quality according to the quantification of its chemical attributes in different management systems and time of use of liquid pig manure. Chemical attributes of an Entisol were evaluated in three layers. The treatments consisted of a native forest area (NF) and three farming areas: perennial Tifton 85 (Cinodon spp.) pasture with successive use of pig manure for 4 (PP4) and 16 years (PP16) and annual cultivation of grains in no-till farming for 16 years (NTF), located in a rural property in the municipality of Três Passos, Rio Grande do Sul, Brazil. The use pig maure in PP4 and PP16 increased the Cu and Zn content in the soil surface layer when compared to the native forest area, indicating significant contribution of pig manure in the increase of these elements in the soil. The successive application of pig manure in PP16 increased the P content in the 0-5 cm layer above the critical environmental limits (CEL-P), which could the soil quality. The cation exchange capacity (CEC), total organic carbon (TOC) and Cu, Zn and P in soil are the chemical attributes that can be used as soil quality indicators.